AN ANALYSIS OF METONYMY IN COLUMN WORLD OF JAKARTA POST NEWSPAPER - Nopriansah -; Weni Sri Apriliana (UNIVED Press, 2015)
This study is a focus description study, in which the researcher gave an attempt to analyze the meaning of each of the sentences or utterances that use metonymy. The theory by Panther and Thornburg (2004) was used to analyze the data. The analysis of the data were based on three types of metonymy. They are the referential metonymy, the predication metonymy and the illocutionary act metonymy. The results revealed that, from the aforementioned three types of metonymy, the types of metonymy that are frequently used are the referential and the predication because the two types are related to language newspaper which usually made with retelling a story. And three types at the least are the type that the illocutionary act because of the types associated with the act including in the pragmatic study cause language news rarely use direct act. Keywords :Metonymy, Discourse, Speech Acts, Structure, Lexicon